PEMBUATAN FILM PENDEK ACTION FORMAT 3D YANG BERJUDUL WAR OF MACHINE MENGGUNAKAN AUTODESK 3DS MAX - Rangga Gading Satria Gading Satria; Dimas Aulia Trianggana; Dewi Suranti (UNIVED Press, 2015)
This study is to make a short film makin gaction 3D format called War of Machine using Autodesk 3ds Max.The specific objective of this study is to find out how to explain ingreator dinances of film making with housing specifications. In the short-action filming 3D format called War of Machine using Autodesk 3ds Max technique used is the character rigging techniques. The experiment was conducted in a computer laboratprium of Dehasen University. Results and analysis are conducted show that film making with simple and basic techniques in video editing was very easy and user friendly.Keywords: short film entitled action 3D format War of Machine using Autodesk 3ds Max